2019
DOI: 10.3390/horticulturae5040068
|View full text |Cite
|
Sign up to set email alerts
|

Association of Indolebutyric Acid with Azospirillum brasilense in the Rooting of Herbaceous Blueberry Cuttings

Abstract: Association between auxins and plant growth-promoting bacteria can stimulate root growth and development of fruit crop nursery plants, and can be a promising biological alternative to increase the rooting of cuttings. The objective of this study was to assess the viability of producing ‘Powderblue’ blueberry nursery plants from cuttings using different doses of indolebutyric acid (IBA) in association with Azospirillum brasilense. The following treatments were tested: 0 (control); 500 mg L−1 of IBA; 1000 mg L−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
7
1
Order By: Relevance
“…Using cuttings for propagation can be an effective strategy to bring wild berries closer to farmers and initiate their cultivation. However, some studies have reported that blueberries have a low rooting rate, which limits their propagation (Braha & Rama, 2018;Koyama et al, 2019). In the current study, the rooting percentages of all five accessions were greater than 90% aer treatment with 2,000 mg L −1 IBA.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Using cuttings for propagation can be an effective strategy to bring wild berries closer to farmers and initiate their cultivation. However, some studies have reported that blueberries have a low rooting rate, which limits their propagation (Braha & Rama, 2018;Koyama et al, 2019). In the current study, the rooting percentages of all five accessions were greater than 90% aer treatment with 2,000 mg L −1 IBA.…”
Section: Discussioncontrasting
confidence: 38%
“…e results showed that the rhizogenic capacity and shoot development of the cuttings varied owing to the influences of the germplasm and IBA concentration. IBA at high concentrations has been reported to potentially have inhibitory effects on vegetative propagation (Koyama et al, 2019), although such effects may vary because of factors such as genetic variation among species or cultivars (An et al, 2018) and variations in the application method (liquid or powder) (Peña et al, 2012) and type of explant (apical, middle, or basal) (An et al, 2018). erefore, for the propagation…”
Section: Discussionmentioning
confidence: 99%
“…However, with CCK and CCR, root length was similar or was even inhibited under the same treatment. Another study conducted reveled that indolebutyric acid increased the number of roots and root length of blueberry cuttings, but on the contrary, no effect was observed in rooting percentage and survival percentage of the cuttings [56]. Planting dates and NAA treatments could significantly improve root number and length [57], yet under our experimental conditions, it was determined that planting time did not influence root number or root length.…”
Section: Discussionmentioning
confidence: 71%
“…The first contribution in this section explored the "Association of Indolebutyric Acid with Azospirillum brasilense in the Rooting of Herbaceous Blueberry Cuttings" by Koyama et al [10]. The use of plant growth-promoting rhizobacteria (PGPRs) can be a promising biological alternative for increasing the rooting of blueberry (Vaccinium sp.)…”
Section: Fruit Cropsmentioning
confidence: 99%